Heterogeneous Effects of Blood Pressure Screening - Fabrice Kämpfen; Irene Mosca (Institute of Labor Economics (IZA), 2024)
This is the first study that investigates the heterogeneous effects of blood pressure (BP) screening on subsequent changes in BP in a high-income country. We use data from clinical health assessments carried out in 2010 (baseline) and 2014 (follow-up) as part of a nationally-representative longitudinal study on ageing in Ireland. We employ a Regression Discontinuity Design (RDD) by comparing outcomes at follow-up on either side of the BP cutoff that separates normal to abnormal BP at baseline. We find that the BP screening reduces BP at follow-up among those who at baseline do not report a previous hypertension diagnosis, with larger and more precisely estimated effects for males, middle-age individuals (as opposed to older individuals) and individuals without public health insurance coverage. However, we find no effects when we include in the analysis individuals who at baseline report a previous hypertension diagnosis. Overall, our analysis suggests that the effectiveness of the screening likely depends on whether the information on the outcome of the screening provided to individuals is new to them or not.
Keywords: C21; I12; I18; 330; health screening; hypertension; blood pressure; undiagnosed individuals; non-communicable diseases; regression discontinuity design; ireland; high-income country